Integrative and Complementary Practices in women's health care (Research, Society and Development, 2020)
Objective: to analyze the use of  Integrative and Complementary Practices (ICPs) in comprehensive care for Women's Health. Method: Narrative review of the literature, carried out on the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and PubMed databases. Using the descriptors: “Complementary Therapies” AND “Women's Health”, with no time frame. Ten articles were selected and submitted to Bardin's content analysis. Results: The first publication was in 2010, and 80% of the studies were developed by Nursing. Three categories emerged: integrative and complementary health practices, impacts on women's health and the performance of health professionals. Evidence has shown that the health model remains disease-centered. However, among the ICPs, music therapy, hydrotherapy, aromatherapy, foot reflexology, scalding, use of medicinal plants, among others, stand out. ICPs were used to relieve physical symptoms, pain in general, with emotional and psychological benefits, in the parturition process, during prenatal care, neoplasms and in climacteric signs. Health professionals who frequently use these practices, in their professional practice, in health services are doctors, nurses, physiotherapists and doulas. Conclusion: Integrative and Complementary Health practices can be used in all cycles and phases of women's health, therefore, integrating the knowledge of PICS in training and qualification are essential for the provision of comprehensive assistance to women's health.